Keberterimaan Terjemahan Alat Kohesi pada Novel I Am Number Four dalam Bahasa Indonesia - Iswanto, Joko (TALENTA, 2025)
This study aims to the acceptability of the translation of device cohesion in the novel I Am Number Four“No. 4 adalah Pahlawan bagi Generasi Ini”. The theory of cohesion as the basic of this study is proposed by Halliday dan Hasan (1976). The assessment of acceptability of translation quality used instrument of translation acceptability model by Nababan (2012). The method of research was a descriptive qualitative. While the source of data in this research were words and phrases were taken in the novel I Am Number Four (ST) and its translation “No. 4 adalah Pahlawan bagi Generasi Ini” (TT). The data were words and phrases belonging to grammatical cohesion, the total was 93 those consist of 71 words and 22 phrases in ST and 30 words and 63 phrases in TT. The results of the research on 93 data showed that 83 data were considered acceptable 89.25 %, 6 less were considered acceptable 6.45 %, and 4 were considered unacceptable 4.30 %.